Subjective Well-Being Pada Individu yang Komitmen Bersedekah Di Kota Makassar - Amirah Aminanty Agussalim (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2015)
This study aims to determine the differences level of subjective well-being (SWB) in individuals who committed charity in the city of Makassar. Subjects in this study were members of the Community Charity Month Early in Makassar, a total of 30 subjects. This study used quantitative research methods. The research instrument consisted of a questionnaire Alms commitment to see the commitment of individuals in charity and scale of Positive Affect Negative Affect Schedule ■ Expanded Form to measure positive and negative affect on indivdu and Satisfaction with Life Scale used to measure the level of individual life satisfaction. Subjects in the study were measured three times to determine differences in the level of SWBBased on the analysis of research data, to the cognitive and affective aspects of the show that there was no significant difference in the level of SWB is based on three types of charity commitments are measured before the charity, a week after charity, and two weeks after the charity, individuals who committed to charity have a relatively constant level of SWB. Keywords: Subjective Weil-Being, Charity, Charity Commitment